Latest advances and status analysis of nanomaterials for microalgae photosystem, lipids and biodiesel: A state of art - Reetu; Clifford M.; Prakash R.; Rai M.P. (My University, 2025)
Growing energy demand and exhaustion of mainstream fuels lead to the need for renewable energy sources. Microalgae possess remarkable properties including carbon dioxide mitigation, accruing intracellular lipids and an ability to thrive in harsh conditions, which makes them a potential feedstock for biofuel production. However, narrow photosynthetic light absorption and limited lipid production are major bottlenecks that remain key obstacles to practical commercialization. Therefore, previous research has suggested that the use of nanomaterials could overcome these restrictions. Their extraordinary physicochemical characteristics, as well as an enormous surface area, can be exploited in practical applications. Some nanomaterials are reported to promote the photosynthetic efficiency of microalgal cells, which in turn increases biomass production. Furthermore, by using specific nanoparticles, an advancement in lipid production can also be achieved. A specific group of nanomaterials target the upregulation of the key enzymes involved in the lipid synthesis pathway, which in turn leads to higher lipid production and accumulation. However, most of the studies deciphered their toxic behaviour. This review endeavours to deliver an overarching insight into the impact of nanomaterials on microalgae photosynthesis, lipid and biodiesel production. It also focuses on the use of algal residue in possible applications that makes the process largely sustainable with zero waste. This review surveys the state of the combination of nanotechnology and microalgae to achieve high biomass and lipid production along with other valuable products. © 2022 Elsevier Ltd.